Voiding urosonography: Contrast-enhanced ultrasound cystography to diagnose vesico-ureteric reflux: A pilot study - Ramesh Babu; Vinu Gopinath; Venkata Sai (Wolters Kluwer Medknow Publications, 2015)
We report two children with hydronephrosis, in whom we have utilized voiding urosonography (VUS) in the evaluation of vesico-ureteric reflux. With wider availability of ultrasound contrast agents and high-end ultrasound machines, VUS is likely to become a popular tool to diagnose or exclude VUR.